Landscape [re]Mediation : a strategized landscape intervention that explores the functional, aesthetic and cultural value of trees as design informant - Shand, Dayle Lesley (University of Pretoria, 2019)
Mini Dissertation (ML (Prof))--University of Pretoria, 2018.